2015
DOI: 10.1007/s12576-015-0364-9
|View full text |Cite
|
Sign up to set email alerts
|

Altered urinary sodium excretion response after central cholinergic and adrenergic stimulation of adult spontaneously hypertensive rats

Abstract: In this study, we hypothesized that blunting of the natriuresis response to intracerebroventricularly (i.c.v.) microinjected cholinergic and adrenergic agonists is involved in the development of hypertension in spontaneously hypertensive rats (SHR). We evaluated the effect of i.c.v. injection of cholinergic and noradrenergic agonists, at increasing concentrations, and of muscarinic cholinergic and α1 and α2-adrenoceptor antagonists on blood pressure and urinary sodium handling in SHR, compared with age-matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 52 publications
3
17
0
Order By: Relevance
“…These effects are independent of changes in renal hemodynamics [46,49]. Taken together with previous findings [10,25,28,30,50,51], the current study demonstrated that bilateral renal denervation delays the development of arterial hypertension associated with reduced sodium reabsorption by the proximal and/or post-proximal tubule segments in this particular experimental model of developmental programming.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These effects are independent of changes in renal hemodynamics [46,49]. Taken together with previous findings [10,25,28,30,50,51], the current study demonstrated that bilateral renal denervation delays the development of arterial hypertension associated with reduced sodium reabsorption by the proximal and/or post-proximal tubule segments in this particular experimental model of developmental programming.…”
Section: Discussionsupporting
confidence: 88%
“…Inc, MA, USA), respectively. Thereafter, animals were anaesthetized with ketamine and xylazine injected intraperitoneally and sacrificed by cardiac puncture; urine and plasma samples were stored for analysis [3,4,6,7,29,30]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal and Diets -The experiments were conducted as described in detail previously (Lutaif et al, 2015) on an age-matched female and male rats of sibling-mated Wistar HanUnib rats (250-300 g) that were allowed free access to water and standard rodent chow (Nuvital, Curitiba, PR, Brazil).…”
Section: Materials and Methodologymentioning
confidence: 99%
“…It has long been known that there is an association between the CNS and the control of water and salt excretion by the kidneys [1,13,14]. Adrenergic stimulation of the septal area, lateral hypothalamus, subfornical organ, and the anterior region of the third ventricle induces dose-related natriuresis accompanied by, but to a lesser extent, kaliuresis [9,[15][16][17][18][19][20][21]. On the other hand, studies have shown that electrolytic lesion of the hypothalamic regions in conscious rats reduces salt intake, and the pressor response to cholinergic and noradrenergic microinjection into the median preoptic nucleus [22].…”
Section: Introductionmentioning
confidence: 99%